Investigating the functional and metabolic role of carnitine in the diabetic heart using hyperpolarized MRI - Savic, D (2018)
Diabetes increases the incidence of myocardial infarction and heart failure, which are leading causes of mortality in diabetic patients. L-carnitine levels are decreased in the plasma of diabetic patients and L-carnitine supplementation has been shown to have protective effects. L-carnitine transports fatty acids into the mitochondria allowing for subsequent —-oxidation, but it can also export acetyl-CoA from the mitochondria through acetylcarnitine and thereby relieve PDH-flux. The aim of this thesis was to explore the effects of modulating L-carnitine levels on in vivo metabolism and function in the diabetic heart. Hyperpolarized MRI was used to assess metabolism, while CINE MRI was used for the assessment of cardiac function. A Langendorff method was used to determine the ex vivo effect of L-carnitine on functional recovery post-ischemia. Different diabetic models were initially investigated to find the most appropriate model in which to modulate L-carnitine levels. A neonatal model of diabetes showed decreased aerobic to anaerobic metabolism (50 %) in conjunction with functional impairment, which could be reversed with Glibenclamide treatment. A fasted streptozotocin induced rat model showed superior SNR on MRI and was pursued further. PDH-flux and alanine metabolism were decreased (>60%) with diabetes which coincided with functional impairments. Sustained hyperglycaemia for four weeks led to an elevation in lactate and alanine (>140 %), while also elevating stroke volume. L-carnitine treatment (3 g/kg/day, i.p.) elevated acetylcarnitine (AC) levels (219 %) and slowed down the progression of hyperglycaemia in diabetes, while elevating PDH-flux (51 %), allowing for improved diastolic function (16 %) in vivo, and improved functional recovery post-ischemia ex vivo (270 %). However detrimental effects were observed in control animals treated with L-carnitine. Daily Mildronate treatment, which inhibits L-carnitine uptake, reduced AC levels (52 %) and elevated PDH-flux (214 %) in the diabetics. These metabolic changes were not accompanied by functional changes. However, improved ex vivo functional recovery post-ischemia (34 %) was observed, but did not reach the level of recovery that L-carnitine had on the ex vivo heart. This work has clarified that the use of L-carnitine treatment in diabetes can enhance carbohydrate metabolism and is more beneficial than decreasing L-carnitine levels with Mildronate. This work has shown the potential for using hyperpolarized and CINE MRI in better understanding the mechanism of L-carnitine’s effect on the diabetic heart, and it may provide new insights into novel therapeutics.